2001
DOI: 10.3758/bf03194418
|View full text |Cite
|
Sign up to set email alerts
|

Temporal bisection with trial referents

Abstract: There is general agreement among the quantitative models for time (see Allan, 1998) that mean perceived time ( μ t ) is a power function of clock time with an exponent close to 1.0,and that variability in perceived time (s t ) is proportional to mean perceived time,The proportionalityconstant g is known as the Weber fraction, and the proportionality relation is often referred to as scalar variability. This scalar property between the standard deviation and the mean results in distributions of perceived time th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 24 publications
6
70
0
Order By: Relevance
“…What is less clear is what the data say about the relation of subjective to objective time, or whether time is under-or over-estimated as opposed to veridically perceived. The same data could have arisen if β = 1 (i.e., μ(t) = t) and the assumption that S mp = μ(t mp ) is removed, implying that observers perceive duration veridically but for some reason they do not set the anchor at μ(t mp ) during the training phase (Raslear, 1985;Allan and Gerhardt, 2001;Allan, 2002a,b). And the same shift could have been caused also with μ(t) = t and by reinstating the assumption that S mp = μ(t mp ) if observers had a non-null indifference region (i.e., δ = 0) and responded with bias when undecided ( Figure 5).…”
Section: Summary and Discussion Of Single-presentation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…What is less clear is what the data say about the relation of subjective to objective time, or whether time is under-or over-estimated as opposed to veridically perceived. The same data could have arisen if β = 1 (i.e., μ(t) = t) and the assumption that S mp = μ(t mp ) is removed, implying that observers perceive duration veridically but for some reason they do not set the anchor at μ(t mp ) during the training phase (Raslear, 1985;Allan and Gerhardt, 2001;Allan, 2002a,b). And the same shift could have been caused also with μ(t) = t and by reinstating the assumption that S mp = μ(t mp ) if observers had a non-null indifference region (i.e., δ = 0) and responded with bias when undecided ( Figure 5).…”
Section: Summary and Discussion Of Single-presentation Methodsmentioning
confidence: 99%
“…Some modifications of the temporal generalization and bisection tasks turn them into paired-comparison methods, and the models discussed here apply to them too. For instance, the roving standard task of Allan and Gerhardt (2001) or Rodríguez-Gironés and Kacelnik (2001) presents in each trial a short and a long exemplar (which vary across trials) so that observers compare the test duration with the current exemplars. Similarly, the episodic temporal generalization task of Wearden and Bray (2001) presents a variable standard in each trial which is the reference for the observers' current judgment.…”
Section: Paired-comparison Methodsmentioning
confidence: 99%
“…Several previous studies have indeed found good superposition under a wide range of conditions (e.g. Allan, 2002b;Allan & Gerhardt, 2001;Allan & Gibbon, 1991;Penney et al, 1998Penney et al, , 2000Wearden & Bray, 2001;Wearden & Ferrara, 1996;Wearden et al, 1997) although small departures are sometimes observed (Penney et al, 1998(Penney et al, , 2000Wearden et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Various versions of such tasks have been employed, allowing manipulation of factors such as the memory demands of the task (e.g., Allan, 2002a;Rodriguez-Girones & Kacelnik, 2001;Wearden & Bray, 2001) or the number of times a given duration is repeated within an experiment (e.g., Allan & Gerhardt, 2001). The stimulus durations that are employed are typically short enough (less than 1 or 2 s) to prevent chronometric counting.…”
mentioning
confidence: 99%
“…Allan (2002a) and Allan and Gerhardt (2001) found that the standard of comparison did not change even when the referents changed from trial to trial. Their subjects used the range of referents encountered over many trials to establish a standard that was employed on every trial, regardless of the referents given on that trial.…”
Section: Resultsmentioning
confidence: 99%